Effect of Delayed Harvesting on the Quality of 'Cuixiang' Kiwifruit - Wen PENG; Min ZHANG; Xinyi LI; Qinyu ZHAO; Xiangyu SUN; Tingting MA (Shipin gongye ke-ji)
This paper took the medium-early-maturing variety 'Cuixiang' kiwifruit as the research object. The normal harvested fruits were the control group, and the fruits with 1~4 weeks of delayed harvesting were the treatment group. The control and treatment fruits were subjected to three treatments: at harvest (AH), room temperature maturation (RTM) and low-temperature maturation (LTM). In this paper, the effects of delayed harvesting on the quality of 'Cuixiang' kiwifruit based on fruit shape and weight, physicochemical indexes, storage characteristics, sensory and nutritional qualities were analyzed. The results showed that with delayed harvesting, the fruit shape and weight of kiwifruit were not affected, and the hardness decreased significantly (P<0.05). Delayed harvesting significantly increased the sugar-acid ratio in the AH group and decreased the soluble solids content in the RTM and LTM groups (P<0.05). Delayed harvesting for 1 week effectively suppressed the development of rot and chilling injury. Delayed harvesting significantly reduced the b* value of fruits (P<0.05), but maintained the textural quality of fruits in the LTM group, significantly reduced the ascorbic acid content of fruits in the AH group (P<0.05), and slowed down the degradation of ascorbic acid in the LTM fruits and maintained their antioxidant capacity. This study can provide a theoretical basis and reference for the application of delayed harvesting in kiwifruit.